Comparison of skeletal age and various physical and motor factors with the pubescent development of 10,13, and 16 year old boys - Clarke, H Harrison; Degutis, Ernest W (Research Quarterly. American Association for Health, Physical Education and Recreation, 1962)
The purpose of this study was to compare the skeletal ages and various physical and motor factors with the pubescent development of 10, 13, and 16 year old boys. The findings of this study indicated that physical maturation was differentiated most effectively at 13 years of age, although it was not so sensitive to maturational changes as was skeletal age; at 16 years, maturational differentiation was much more limited; and at 10 years, little or no value can be attributed to this method. The 13 and 16 year old boys who were advanced in pubescent development had higher mean scores on all physical and motor tests studied with few exceptions; generally, the differences between the means were significant. In terms of physique types, the only significant difference was found at 16 years of age, where a greater percentage of ectomorphs was found in pubescent group 4 than in group 5. © 1962 Taylor & Francis Group, LLC.
Keywords: dept.rec